2005
DOI: 10.1016/j.crte.2005.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of regional variations in salinity and temperature in a coral reef lagoon, New Caledonia

Abstract: The variability in salinity and temperature in the southwest lagoon of New Caledonia (2,100 km 2 ) under non-storm conditions is analyzed using a 4-year data set (1997)(1998)(1999)(2000)(2001). Seasonal and interannual variations in salinity are amplified near shore.Temperature is larger in bays than in the open lagoon during summer, the reverse is true in winter. El Niño Southern Oscillation (ENSO) related nearshore temperature variations parallel those at regional scale, but with seasonal variations amplifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…Fig. 2a Interannual salinity and SST variations in the Southwestern tropical Pacific are linked to ENSO (Gouriou and Delcroix, 2002;Ouillon et al, 2005). Thus, SST covariant changes in SSS (and d 18 O sw ) occur on seasonal and interannual time scales.…”
Section: Tahiti French Polynesiamentioning
confidence: 95%
“…Fig. 2a Interannual salinity and SST variations in the Southwestern tropical Pacific are linked to ENSO (Gouriou and Delcroix, 2002;Ouillon et al, 2005). Thus, SST covariant changes in SSS (and d 18 O sw ) occur on seasonal and interannual time scales.…”
Section: Tahiti French Polynesiamentioning
confidence: 95%
“…However, there was a clear increase in Chl-a concentration regionally, indicating that there was an important effect from ENSO on the Venezuelan coast. Westmacott et al (2000) and Ouillon et al (2005) reported that large amounts of precipitation and low salinity are possibly the consequence of the "cold phase" of ENSO, known as "La Niña" and asserted that a decrease in salinity concentration is the second most common trigger for coral reef bleaching.…”
Section: Discussionmentioning
confidence: 99%
“…The OC3 Modis algorithm (1) uses 3 spectral bands at 443, 488 and 551 nm to determine chl a concentration (Chl). 4 (2) where R=log 10 (max(R 443 ,R 488 )/R 551 ), for a chl a range between 0.015 and 64 mg/m 3 .…”
Section: Evaluation Of the Algorithmsmentioning
confidence: 99%
“…Coral reef lagoon systems are very sensitive to anthropogenic (nutrients, mining) perturbations [1] as well as to longterm climatic changes which are amplified in lagoons [2]. Sea surface chlorophyll is a proxy of phytoplankton biomass and is a direct integrator for the nutrient status of water masses and chlorophyll monitoring by satellite will greatly expand our knowledge of the functioning of coral reef lagoons [3].…”
Section: Introductionmentioning
confidence: 99%